2016
DOI: 10.1002/cctc.201501397
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Linker Length on P450 Fusion Constructs: Activity, Stability and Coupling

Abstract: Three different reductases have been fused to CYP153 monooxygenase from Marinobacter aquaeolei. The most promising candidate has been analysed in terms of its linker part, which connects the reductase with the haem domain through sequence alignment of the corresponding reductase family CYP116B. To improve the artificial fusion construct, the linker length has been varied, thereby only altering the non‐conserved middle part of the linker. This way seven artificial fusion constructs have been engineered, which v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
(98 reference statements)
1
30
0
Order By: Relevance
“…It can catalyze enantio‐ and regioselective hydroxylations, and it consists of two catalytic domains: the CPR, which is a NADPH‐dependent FAD‐ and FMN‐containing reductase domain, and a monooxygenase heme domain. In some studies, various artificial reductase–monooxygenase fusions were made, either to improve stability and/or to improve electron‐coupling efficiency . Sabbadin et al.…”
Section: Enzyme Fusions In Biocatalysismentioning
confidence: 99%
“…It can catalyze enantio‐ and regioselective hydroxylations, and it consists of two catalytic domains: the CPR, which is a NADPH‐dependent FAD‐ and FMN‐containing reductase domain, and a monooxygenase heme domain. In some studies, various artificial reductase–monooxygenase fusions were made, either to improve stability and/or to improve electron‐coupling efficiency . Sabbadin et al.…”
Section: Enzyme Fusions In Biocatalysismentioning
confidence: 99%
“…This is a great improvement on growing cells where the product concentration and the productivity were 0.08 g L −1 and 2.6 mg L −1 h −1 respectively under equal bioreactor conditions and similar optical densities. P450 RhF constructs in the corresponding cell lysates were analyzed by CO difference spectroscopy using excess NADPH as the reducing agent (Page S3, Supporting information) . This spectrum was compared to a traditional P450 CO difference spectrum and showed equivalent absorbance at 450 nm, indicating correct fusion and function of the election delivering partners with the haem domain of P450 RhF (Table S6, Supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…This comparison suggested that residues 1-23 probably functioned as the membrane anchor and should be dispensable in terms of catalytic activity, so N-terminal trimming was carried out as shown in Figure 6. The linker determines the interaction between the P450 and BMR domains thus facilitating electron flow [69][70][71] and reducing its length by just six residues can abolish the activity of the fusion enzyme [49]. We therefore chose a linker containing 29 amino acids.…”
Section: Cloning Strategymentioning
confidence: 99%